PENERAPAN MODEL RANTAI MARKOV DALAM PERHITUNGAN PREMI ASURANSI LONG TERM CARE UNTUK PENYAKIT JANTUNG DI PULAU SUMATERA - Lestari, Fuji; Sumarna, Nur Alvyanti (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Health insurance is insurance that provides health benefits in the form of cash compensation for medical and treatment costs. One of the health insurance products is Long Term Care (LTC) insurance. Long Term Care insurance provides compensation for the insured who requires medical care or for those suffering from chronic illnesses or physical disabilities that cannot be covered by other insurance. This study discusses the calculation of premiums for heart disease, including hypertension and diabetes, for the LTC insurance product Annuity as a Rider Benefit using a multi-state model application from the Markov Chain model. The multi-state model used includes healthy, sick, and deceased states, with the assumption that there is no transition from sick to healthy. The premium calculation is based on the Markov chain with a transition probability matrix using heart disease prevalence data in Sumatra Island in 2018. The case study in this research includes males and females aged 25, 35, and 45 years, with premium payment periods of 5, 10, and 15 years. The death benefit is IDR 500,000,000.00, the care benefit is IDR 100,000,000.00, and the interest rate is 6.25%. Based on age, the calculation of the annual net premium for Long Term Care insurance, the Annuity as a Rider Benefit product for heart disease in Sumatra Island, shows that men generally have higher premiums compared to women, with a range of 0.9598 to 1.0028 times. Meanwhile, based on the premium payment period, men also have higher premiums than women.